Inequality matters - Kapoor, Radhicka (2013)
If economic growth was the only factor that mattered for poverty reduction, we should have witnessed greater poverty reduction. Also, states with the highest growth rate should have performed the best in terms of poverty reduction. The pace of poverty reduction is influenced both by changes in income distribution overtime and by the shape of the initial distribution. This empirical analysis shows that the task of poverty reduction in India is seriously challenged by rising inequality. In addition to the one-shot instant impact on poverty from a pure redistribution effect, improvements in distribution of income have a long-run effect derived from an increase in the growth elasticity of poverty. This gives us a strong case for prioritising distribution and making income distribution more equal before embarking on a high growth path. - Reproduced.
Keywords: Poverty